Students’ Perception of The Use of Mobile Application Pingolearn in Learning to Speak English - Fatimah, Dwi; Ismahani, Siti (Jayapangus Press, 2025)
This study aims to explore students' perceptions of using the Pingolearn mobile application as a learning tool to improve English speaking skills. Rapid technological advances have encouraged many students to use application-based learning tools to improve the quality of students' English speaking skills. This research focuses on finding out the effectiveness and benefits of the Pingolearn application when used by students. A qualitative approach with the case study method used. This research involved 30 students from Prayatna Medan High School, one of the high schools in Medan City, consisting of 18 female students and 12 male students. The selection of participants in this study used a purposive sampling technique. Data collection techniques include observation, questionnaires and interviews to explore students' experiences and perceptions of the Pingolearn application. After the data was collected, the researcher analyzed it using Thematic Analysis. The research results show that the majority of students responded positively to the Pingolearn application, especially in growing self-confidence when speaking. They also stated that interactive features, such as AI voice dialogue and conversation simulations, were very interesting and useful. However, there were several challenges that faced students when using them. These findings indicate that Pingolearn is a mobile-assisted learning tool that can be used in English speaking learning to improve English language skills. The results of this study confirm that the use of technology in language learning has great potential to significantly increase students' motivation, self-confidence and speaking abilities.